Outcomes 30 days after ICU admission: the 30DOS study. (2nd November 2017) - Wise, Robert; de Vasconcellos, Kim; Skinner, David; Rodseth, Reitze; Gopalan, Dean; Muckart, David; Banoo, Zohra; Bisseru, Tashmin; Blakemore, Steve; de Meyer, Jenine; Faurie, Michael; Govender, Kom; et al.
Abstract : Background: The spectrum of illness and long-term outcome of critically ill patients admitted to intensive care units (ICUs) in South Africa remains largely unknown. Objectives: This study was designed to provide data on ICU outcomes and disease burden in public sector ICUs in KwaZulu-Natal. The primary objective was to describe 30-day mortality of all patients admitted to participating sites. Secondary objectives included clinical demographics and spectrum of illness amongst these patients, and testing a template to demonstrate feasibility of such data collection. Methods: 30DOS was a multicentre, prospective, observational cohort study conducted over 30 days. An a priori decision was made to report study results separately for adults and paediatric patients. This article reports the results for adult patients. The complete 30-DOS study included 11 ICUs in six hospitals. All adult patients admitted to study ICUs were included. Patients were followed up telephonically by a research assistant. Data on patient demographics, preadmission functional scoring, injury severity scoring, co-morbidities, admission diagnosis/es, organ support, and outcome were collected. Results: A total of 228 adults were included. The majority of admissions (73.7%) occurred on an emergency basis, with 68.4% occurring in the postoperative period. Approximately half were for non-communicable disease (49.6%), followed by trauma (29.0%) and infectious disease (21.5%). There were a total of 59 (25.9%) deaths within the first 30 days after admission. In-ICU mortality was 19.7%. There were 12 (5.3%) in-hospital deaths following discharge and two (0.9%) out-of-hospital deaths. Thirty-day survival was known for 174 (76.3%) admissions with a 33.9% mortality rate. Conclusion: Overall in-ICU mortality was 19.7% with a large trauma burden in a young population. Thirty-day mortality was 33.9%. Information pertaining to patient demographics and spectrum of illness provided novel information to further the understanding of the demand placed on critical care resources within South Africa.